Migration and Social Integration: Experiences of Internal Migrants in Makassar City - Sakti, Muhammad Indra (Generasi Sains Indonesia, 2025)
Migration plays a vital role in shaping urban growth and cultural diversity in Indonesia, with Makassar becoming a key destination for internal migrants from Eastern regions. This study explores migrant experiences in adapting to new social, cultural, and economic contexts, emphasizing opportunities and challenges in urban integration. Migration is viewed not merely as physical relocation but as an ongoing negotiation of identity and belonging. Using a qualitative descriptive method with purposive sampling, the study involved 40 respondents, including students, workers, and families. Data were collected through interviews, focus group discussions, observation, and document analysis, then analyzed thematically to identify integration patterns in education, employment, housing, and social life. Results show most migrants are aged 18–35, with balanced gender representation. Education and employment are key to successful adaptation, as migrants with higher education and formal jobs integrate more easily. However, housing remains problematic, with many relying on temporary residences. Social participation levels are moderate to high, though 15% of respondents face cultural or structural barriers. Overall, Makassar exhibits strong potential as an inclusive urban hub, where community openness and cultural adaptability promote integration, yet improved housing and equitable policy support are essential for sustainable cohesion.